KEBANGKITAN KEKUATAN NORMATIF TIONGKOK DI EROPA: STUDI KASUS PENGARUH TIONGKOK TERHADAP HUNGARIA DALAM UNI EROPA PASCA INISIASI 16 + 1 - Bagus Rahmadia Pranawa; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Hungary, under Prime Minister Viktor Orbán, through various policies, has occupied a unique position as a disruptive actor in the European Union. The EU considers that Hungary is no longer in line with EU values and has created complicated conditions for the EU. One form of Hungarian policy that has had a disruptive impact on the EU is Hungary's political support for China within the EU, even though China is considered a rival of the EU and has differing values than the EU. This research aims to explain why Hungary decided to support China. In this study, the authors use the concept of normative power, which analyzes how an actor can affect what is normal in international relations through the spread of universal values and norms. The author uses this concept to analyze the fulfillment of the characteristics criteria and the distribution factors of normative power. The research finds that Hungary has accepted, implemented, and disseminated China’s promoted values and alternative global politics model. These findings are proven through various policies and statements from the Hungarian government. This acceptance resulted in Hungary's deviation from EU values through various policies, including Hungary's policy of supporting China.